The Role of State Parties to the Rome Statute in the Interpretation of the Statute : An Evaluation of Past Practice and Future Prospects - Shilaho, Caroline Vicheti (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2026)
This book offers a groundbreaking and thought-provoking examination of the intricate interplay between the role of State Parties to the Rome Statute in the interpretation of the Statute, particularly when the International Criminal Court (ICC) holds the explicit authority to do so. Utilizing the interpretation rules under Article 31(3) of the Vienna Convention on the Law of Treaties, it demonstrates how State Parties, through their subsequent agreements and practice continue to influence treaty interpretation under the Rome Statute. The book highlights specific examples where State Parties have enacted amendments to the rules and passed resolutions during related ongoing ICC cases, prompting questions about their influence on the ICC's interpretive decisions. The nuanced relationship between State Parties and the ICC in interpreting the Statute is explored, revealing the inherent tension that emerges from the overlapping interpretive roles. It provides insightful recommendations for navigating and alleviating such tensions.